Tools to support trainers, learners and professionals for a good practice of plant wild harvesting - Barata, Ana Maria (2016)
PLANT WILD: Forest Plants Wild Harvesting Learning in Europe, a Grundtvig Learning Partnership Association, with the aim of promoting employment opportunities in rural and mountainous areas and sustainable wild harvesting techniques, generating best training practices to obtain environmental and economical sustainability and determining tools to support rural populations, trainers, learners and professionals. The objective of the project was the establishment of a framework between 4 partners from Lithuania, Portugal, Spain and Turkey, for designing, planning and developing the necessary tools applicable to VET Institutions (Vocational Education and Training) and SME as well as to adults of marginal rural and mountainous areas in relation with Medicinal and Aromatic Plants (MAP)’ wild harvesting